Raychem RPG Ltd : strategic transformation - Karna, Amit, (SAGE Business. Cases., 2019)
The case describes the strategic transformation at Raychem RPG Ltd (RRL) - a joint venture between RPG group, India and TE Connectivity, USA. The case focuses on the various initiatives by Ramani Kasi, President and a long time employee of RRL.